À l’origine du « rang » canadien - Derruau, Max (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1956)
What is the origin of the type of settlement known in French speaking Canada as the rang ? Is it an import from France or an original Canadian creation ? The System is based on French agricultural customs, but bas been adapted to theNew World and applied with a geometrical strictness unknown in France.